Modelling the dynamics of economic development driven by agricultural growth in Patna Region, India - Rashmi Kumari; V. Devadas (Journal of Economic Structures, 2017)
Regional planning primarily aims at reducing the disparity in socio-economic status of the people, and the wide gulf between urban and rural life. A planning region or an area comprises of many complex structures and behavioural phenomena which more or less change with time due to some external forces acting upon or the internal forces acting within the regional system. While planning for the development of a region, the well-known phenomena and structures within the regional system can be considered. Further, the sustainable economic development of a region can only be achieved by ensuring the optimum utilization of resources. This requires plausible policy planning guidelines and feasible development plan, for which thorough grassroots level investigation is essential. In this present investigation, an attempt has been made to evolve a set of plausible policy guideline and recommendations for the sustainable economic development of Patna region, by considering it as a system, and considering the important control parameters of its subsystems.
Keywords: 330; Agriculture; Regional development; Forecasting; System dynamics; GDP; Simulation